ROTASI DAN KUALITAS AUDIT: EVALUASI ATAS KEBIJAKAN MENTERI KEUANGAN KMK NO. 423/KMK.6/2002 TENTANG JASA AKUNTAN PUBLIK - Siregar, Sylvia Veronica; Fitriany, Fitriany; Wibowo, Arie; Anggraita, Viska (UI Scholars Hub, 2011)
Auditor’s independency is a foundation of the public trust to public accountant profession and is one important factor for assessing audit quality. Regulators expect that the longer the audit tenure (long term relationship between auditor and client), the more often auditor will compromise client’s accounting choices and reporting for his bussines purpose in such a way which will decrease the auditor’s independence. Related to auditor rotation, regulator in Indonesia have made compulsory the rotation for public accountant (AP) every 3 years and public accounting firm (KAP) every 5 years since the end of 2002 by issuing KMK Number 423/KMK.06/2002 dated September 30, 2002 about public accountant services. The objective of this rotation is to prevent independence deterioration of public accountant and public accounting firm. The purpose of this study is to empirically investigate whether the audit tenure has any effect on audit quality and whether rotation for public accountant and public accounting firm will increase audit quality before and after the implementation of KMK number 423/KMK.06/2002. The result shows that KMK No. 423/KMK.06/2002 about audit rotation needs to be evaluated because this study finds no evidence that longer audit tenure and auditor rotation will increase audit quality.